RISK ANALYSIS FOR THE DEVELOPMENT OF XYZ RESIDENCE - Dewie Saktia , Ardiantono; Satrio Hestu , Pidekso (STIE PGRI Dewantara Jombang, 2023)
Population growth in Indonesia creates new challenges for the housing sector. Scarcity in Jakarta and high land prices make residents actively look for alternative housing options in neighboring areas such as Bogor. This causes increased competition between housing development companies, including the XYZ residence project. This research uses the severity index to analyze, evaluate, prioritize and suggest strategies for managing construction-related hazards in the xyz housing area project. From the research results it appears that in the temporal dimension of the XYZ residence construction project, 28 hazards have a very low probability of affecting the project schedule, 14 hazards have a low probability, 2 (two) hazards have a medium probability, 3 (three) hazards have a high probability, and 4 (four) danger has a very high probability. Likewise, the evaluation of the level of risk in the cost aspect of the xyz residence development project shows that 36 risks have a very low probability of influencing project costs, compared to 5 (five) low risks, five medium risks, 1 (one) high risk, and 4 (four) very high risks. For this reason, it is necessary to implement measures that impact the financial dimension.